GELANG BATU, KAPAK BATU, MANIK - MANIK DALAM SUKU SENTANI FUNGSI PRAKTIS DAN MAGIS (Kajian Etnoarkeologi) - Tolla, Marlin (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
Stone bracelet, stone axe and beads are the three most valuable things for the Sentani ethnic group shown from the used of those three things on their rites and ceremony activities. The belief system that they keep and applied on their myths and customary law has made the bracelet, axe and beads have the important role for the implementation of the rites. The practical and magical function of these things depicts the culture of Sentani, a tribe which is still holding their cultural values which has become the precious legacy from the past.